U-Shaped Relationship between Years of Residence and Negative Mental Health Outcomes among Rural-to-Urban Children in Migrant Schools in Beijing, China: The Moderating Effects of Socioeconomic Factors - Cheng, Jin; Wang, Ri-chu; Yin, Xing; Fu, Lin; Liu, Zheng-kui (Frontiers in Public Health, 2017)
Aim: This study aimed to test the relationship between length of residence and mental health in a school-based sample of migrant children who studied in migrant schools. Methods: A total of 7,296 rural-to-urban migrant children were recruited from 58 schools in Beijing and assessed by the State-Trait Anxiety Inventory (STAI) and Children’s Depression Inventory (CDI). Results: A quadratic relationship was found between mental health and length of residence. The results suggested the scores for anxiety and depression were high during the initial resettlement after migrating, then decreased. However, after approximately eight years, the scores increased. Our findings also showed a significant moderating effect of family socioeconomic status (SES) on the relation between mental health and length of residence. Conclusion: This study provided empirical evidence for a better understanding of psychosocial factors on the mental health of migrant children during the process of urbanization in China.